2003
DOI: 10.1007/3-540-44864-0_105
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Atrial Fibrillation Prediction Application Using Genetic Algorithms

Abstract: Paroxysmal Atrial Fibrillation (PAF) prediction viability is a line of research currently being investigated. The definition of new valid parameters for this task may generate various heterogeneous features. Genetic Algorithms (GAs) automatically find a set of parameters to maximize the diagnosis capabilities of a scheme based on the K-nearest neighbours algorithm. This is an efficient way of generating a number of possible solutions for the problem of PAF prediction. The present paper illustrates how GAs, rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…A correlation between the rate and shape of atrial premature complexes and AF onset was mainly found (Thong et al 2004). Finally, other tentative predictors can be mentioned, such as those based on the heart rate variability (HRV) analysis (Shin et al 2006) or genetic algorithms (Mota et al 2003); however, none of them have been capable of providing useful AF predictors.…”
Section: Introductionmentioning
confidence: 99%
“…A correlation between the rate and shape of atrial premature complexes and AF onset was mainly found (Thong et al 2004). Finally, other tentative predictors can be mentioned, such as those based on the heart rate variability (HRV) analysis (Shin et al 2006) or genetic algorithms (Mota et al 2003); however, none of them have been capable of providing useful AF predictors.…”
Section: Introductionmentioning
confidence: 99%